2017
DOI: 10.1111/jgs.15121
|View full text |Cite
|
Sign up to set email alerts
|

The Strategies to Reduce Injuries and Develop Confidence in Elders Intervention: Falls Risk Factor Assessment and Management, Patient Engagement, and Nurse Co‐management

Abstract: In response to the epidemic of falls and serious falls-related injuries among older persons, in 2014, the Patient Centered Outcomes Research Institute (PCORI) and the National Institute on Aging funded a pragmatic trial, Strategies to Reduce Injuries and Develop confidence in Elders (STRIDE) to compare the effects of a multifactorial intervention and an enhanced usual care intervention. The STRIDE multifactorial intervention consists of 5 major components delivered by registered nurses in the role of Falls Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 22 publications
0
54
0
6
Order By: Relevance
“…Results of the joint intervention significantly exceeded that of the CBT or Baduanjin interventions alone ( P < .05). The elderly are susceptible to age-related osteoporosis and are prone to falls, [30,31] and falls are the leading cause of fractures in the elderly. [24] Due to these concerns, elderly housebound may not want to leave their homes.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the joint intervention significantly exceeded that of the CBT or Baduanjin interventions alone ( P < .05). The elderly are susceptible to age-related osteoporosis and are prone to falls, [30,31] and falls are the leading cause of fractures in the elderly. [24] Due to these concerns, elderly housebound may not want to leave their homes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased falls and fracture risks were reported in patients with combination of sarcopenia and OP [ 483 , 506 , 507 ], but, surprisingly, a synergistic effect has not been observed in community-dwelling older men [ 508 ]. Noticeable, RFs for falls linked with HPI-related morbidity include, in addition to altered muscle status, impaired vision, hemodynamic instability (orthostatic and postprandial hypotension), arrhythmias, mental impairment, depression and anxiety [ 457 , 466 , 468 , 509 , 510 ], as well as the numerous medications used. Strong associations between frailty and an increased propensity to falls, fractures and mortality are well documented [ 483 , 511 , 512 , 513 , 514 , 515 , 516 , 517 , 518 , 519 , 520 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…3 Recent studies have shown that adequate selfmanagement may minimize the impact of falls in older adults. [9][10][11][12][13][14][15][16] However, research is lacking on why some older adults engage in self-management actions and behaviors to prevent falls while others do not. 15 Research is needed to explore possible barriers and facilitators to engaging older patients in preventing falls post-hospitalization.…”
Section: Introductionmentioning
confidence: 99%